Application of Behavioristic Theory in Islamic Religious Education Learning - Yuyu Wahyudin (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
This research examines the application of behavioristic theory in Islamic religious education learning. The research method carried out by the author uses qualitative research methods This research concludes that the application of Behavioristic learning theory to PAI learning uses reinforcement, motivation, stimulus and training methods. Meanwhile, changes in student behavior in a positive direction are motivated in learning, interactive, strengthening memory, and tolerance. For scientific development, several suggestions are given: 1) For teachers: to further improve their competencies and be more creative in using teaching methods. 2) for researchers: the results of this research can be used as reference material to further optimize research with the same theme. 3) reader: if not just read, but can be applied together.